Pengaruh Variasi Tekanan dan Jumlah Lubang Injektor Terhadap Besar Sudut Semprotan Bahan Bakar Bioetanol - Naitboho, Asriel; Riwu, Defmit B.N.; Dwinanto, Matheus M. (LONTAR Jurnal Teknik Mesin Undana (LJTMU ), 2024)
This research aims to determine the effect of variations in pressure and number of injector holes on the spraying angle of bioethanol fuel. Bioethanol fuel has become a promising alternative in reducing dependence on fossil fuels. However, proper spray characteristics are required to achieve efficient combustion and low emissions. In this research, experiments were carried out using injectors with varying numbers of holes, namely 6 holes and 12 holes and varying pressures, namely 30 Psi, 40 Psi and 50 Psi. The spray angle of bioethanol fuel is measured and analyzed using appropriate measuring equipment. The research results show that variations in pressure and number of injector holes have a significant influence on the spraying angle of bioethanol fuel. In this case, increasing the pressure tends to increase the spray angle, while increasing the number of holes tends to reduce the spray angle. This understanding is important in designing an efficient and optimal bioethanol fuel injection system. This research contributes to the development of bioethanol fuel technology and provides insight into the influence of pressure and the number of holes in the injector on spray characteristics